1990
DOI: 10.1083/jcb.111.6.3097
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the cellular src protein in interphase and mitotic NIH c-src overexpresser cells.

Abstract: The mouse mAb, mAb 327, that recognizes specifically both pp60v-src and pp60c-src in a wide variety of cells, has been used to determine precisely the various locations of pp60c-src in NIH c-src overexpresser cells, using the technique of immunofluorescence microscopy. In interphase cells, the protein exhibits two main distributions: one that appears uniform and in association with the cell surface and the other that is patchy and juxtanuclear and coincides with the centrosomes. The juxtanuclear aggregation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
87
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 64 publications
12
87
0
Order By: Relevance
“…In line with this these results, we have found that a subpopulation of Fyn-GFP localizes with internalized EGF on endosomes, and this colocalization is more evident after 20 min of internalization. Consistently, Src, another member of the SFKs, also localizes partially to endosomes (55,61,62). Therefore, the three proteins that have been described to interact with the C-terminal region of Tom1L1, namely Fyn, Grb2, and p85, are known to be translocated to endosomes after EGF receptor internalization.…”
Section: Discussionmentioning
confidence: 79%
“…In line with this these results, we have found that a subpopulation of Fyn-GFP localizes with internalized EGF on endosomes, and this colocalization is more evident after 20 min of internalization. Consistently, Src, another member of the SFKs, also localizes partially to endosomes (55,61,62). Therefore, the three proteins that have been described to interact with the C-terminal region of Tom1L1, namely Fyn, Grb2, and p85, are known to be translocated to endosomes after EGF receptor internalization.…”
Section: Discussionmentioning
confidence: 79%
“…S1 D and E). Thus, it is attractive to predict that activation of a Golgi-associated Src kinase (22,23), when activated during the transit of nascent secretory proteins from the ER to the Golgi (3), could induce TGN vesiculation.…”
Section: Modulation Of Src Activity Affects Golgi Compartment Integrimentioning
confidence: 99%
“…1 and 2). A significant fraction of Src is localized to the perinuclear region and the secretory vesicles in neuronal cells (3,4). It interacts with and phosphorylates proteins such as dynamin and synapsin (5-7) and synaptophysin (8) or cellugyrin (9), suggesting a role in the regulation of membrane traffic.…”
mentioning
confidence: 99%